Influence Of The External Environment On The Manifestation Of Silkworm Productivity Traits (Texas Journal of Agriculture and Biological Sciences, 2025)
The article analyzes the influence of the external environment on the manifestation of the silkworm's productive traits. Environmental factors such as temperature, humidity, and light play an important role in the manifestation of the silkworm's productive traits.